HUBUNGAN MINAT DAN SARANA BELAJAR DENGAN HASIL BELAJAR SENI RUPA SISWA SMPN 8 KOTO XI TARUSAN - Drs. Yusron Wikarya, M.Pd., PUTRI SINTIA, Drs. Eswendi, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2017)
This study aims to determine: (1) Interest relationship with the learning result of Fine Arts SMPN 8 Koto XI Tarusan: (2) The relationship of learning facilities with the learning result of Fine Arts SMPN 8 Koto XI Tarusan: (3) Interest relationships and learning tools (4) The relationship of interest and learning facilities together with the learning result of Fine Arts SMPN 8 Koto XI Tarusan. For that done correlational research. The population of this research is all students of SMPN 8 Koto XI Tarusan. The technique of determining the sample by purposive sampling with the number of samples counted 60 people. Collected data were analyzed statistically with multiple correlation analysis using SPSS version 16.0.Kata kunci: minat, sarana, hasil belajar